Effects of deep heat as a preventative mechanism on delayed onset muscle soreness - Symons, T. B.; Clasey, J. L.; Gater, D. R.; Yates, J. W. (The Journal of Strength and Conditioning Research, 2004)
The effects of increased muscle temperature via continuous ultrasound prior to a maximal bout of eccentric exercise were investigated on the symptoms of delayed onset muscle soreness (DOMS) of the elbow flexors. Perceived muscle soreness, upper arm circumferences, range of motion (ROM), and isometric and isokinetic strength were measured over 7 days on 14 college-aged men (n = 6) and women (n = 8). Ten minutes of continuous ultrasound (ULT) or sham-ultrasound (CON) were administered. Muscle temperature was measured in the biceps brachii of both arms. Muscle temperature increased by 1.79° ± 0.49° C (mean ± SD) in the experimental arm of the ULT group. Muscle soreness was induced by a single bout of 50 maximal eccentric contractions. The ULT group did not differ significantly (p < 0.05) from the CON group with respect to perceived muscle soreness, upper arm circumference, ROM, and isometric and isokinetic strength. In conclusion, increased muscle temperature failed to provide significant prophylactic effects on the symptoms of DOMS.